1998
DOI: 10.1016/s0022-5347(01)63747-9
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Tract Obstruction Caused by Childhood Inguinal Herniorrhaphy: Results of Microsurgical Reanastomosis

Abstract: Microsurgical reanastomosis of the seminal tract resulted in high patency and pregnancy rates in cases of seminal tract obstruction caused by childhood inguinal herniorrhaphy. Patients should elect seminal tract reanastomosis or assisted reproductive technology using epididymal or testicular sperm after receiving sufficient information on each treatment modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 17 publications
1
35
0
5
Order By: Relevance
“…[2][3][4][5][6] Injury to the vas deferens is thought to occur when it is adherent to the hernia sac. 7,8 Although difficult to prove, chronic ischemia from our patient's earlier pelvic vascular injury might have contributed to inherent weakness of the tissue, predisposing it to fracture despite careful handling of the cord. Furthermore, although the vasal injury may contribute to obstruction as a source of azoospermia, results of his physical examination demonstrated mild atrophy of the right testicle, suggesting that blood supply may have been compromised during one of his prior operations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[2][3][4][5][6] Injury to the vas deferens is thought to occur when it is adherent to the hernia sac. 7,8 Although difficult to prove, chronic ischemia from our patient's earlier pelvic vascular injury might have contributed to inherent weakness of the tissue, predisposing it to fracture despite careful handling of the cord. Furthermore, although the vasal injury may contribute to obstruction as a source of azoospermia, results of his physical examination demonstrated mild atrophy of the right testicle, suggesting that blood supply may have been compromised during one of his prior operations.…”
Section: Discussionmentioning
confidence: 91%
“…In the most common scenario, an unrecognized injury is revealed only years later in the evaluation of subfertile or azoospermic men who underwent hernia repair during childhood. 7,[9][10][11] Unlike in adults, inguinal hernia repair in children is the most common cause of injury to the vas deferens, 9 which is more delicate and attenuated in infants. Early reports suggested that vasal injury occurs in 0.8% to 2% of pediatric hernia cases.…”
Section: Discussionmentioning
confidence: 99%
“…The microscope was not used for 3 earlier cases. Postoperativel y, spermatozoa were present in the ejaculate in 3 of 6 evaluated cases (50.0%), althoug h the number of these cases is too small for comparison of our reanastomosis outcomes for postinguina l herniorrhaph y patients with those previously reported [9,10]. The success rate of epididymovas ostomy improved markedly af ter the introductio n of mucosa-to-mucosa anastomosis by Silber who used an operative microscope [17].…”
Section: Discussionmentioning
confidence: 99%
“…There is the great discrepancy in vasal diameter between the proximal and distal end of the vas deferens and a relatively long part of the vas deferens may have been resected during the previous inguinal herniorrhaph y. Finally, a longer interval between inguina l herniorrhaph y and reanastomosis of the seminal tract may contribute to low success rate, because with time failure of spermatogenesis may occur secondary to occlusion of the vas [9]. The microscope was not used for 3 earlier cases.…”
Section: Discussionmentioning
confidence: 99%
“…Antonoff et al has pointed out to the higher risk of an inadvertent injury to vas deferens in the absence of a true hernia (68) . Complications that may result in infertility during hernia repair include testicular atrophy, injury to the vas deferens, iatrogenic cryptorchidism, and injury to the fallopian tubes (3,7,15,18,40,(68)(69)(70) . A recent survey declares a 5% infertility rate, medically diagnosed in males 50 years after hernia repair (71) .…”
Section: Solving Complications and Contradictionsmentioning
confidence: 99%